Solid pseudopapillary neoplasm of the pancreas. (Frantz´s tumor) Anatomo-clinical aspects. - Marrero, Gregory; Campos, Maite; Laca, Elisa; González, Daniel; Ruso Martínez, Luis (Cirugía del Uruguay, 2023)
Pseudo papillary tumor of the pancreas, also called Frantz´s tumor, is a very rare disease; between 0.2 and 2.7% of pancreatic carcinomas. Ethiology is unknown; is observed in young women. It´s a tumors with low malignant potential, usually of asymptomatic evolution by long time and the symptoms are due to regional compression: pain or abdominal mass. The possibility of a malignant form is around 15%. Anatomically, they are most frequently located in the tail of the pancreas, followed by the head and body. The treatment is the surgical resection; with an excellent prognosis and a 5-year survival almost 100%. The diagnosis is with pathological study, considering the microscopic appearance and the immunohistochemical profile. Its perform an analysis of the literature and once case of a 21 years old, woman is reported. A complete resection surgery of the tumor was performed and remains asymptomatic at 24 months of follow-up.